PENGARUH NPF, CAR, DAN FDR TERHADAP PROFITABILITAS TAHUN 2016-2019 - Raden Hario Daffa Alaamsah (2021)
This research aims to find out the effect of Non Performing Financing, Capital Adequacy Ratio, and Financing to Deposit Ratio on Profitability which can be measured through the Return On Asets of Islamic Commercial Banks. This research uses independent variables, namely NPF, CAR, and FDR. For the dependent variable is a Profitability. The population on this research is Islamic Commercial Banks in Indonesia. The sample in this research used purposive sampling method. The data in this research collects the financial statement of Islamic Commercial Banks period 2016 to 2019. The tools in this research is classical assumption test, for the analyze technique in this research is data panel regression using E-Views 9 and Microsoft Excel, with hypothesis test, namely t-test, f-test, and r-squared test. The result on this research indicate that NPF has negative effect to profitability, and CAR has a positive effect to profitability. Meanwhile FDR doesn't effect to profitability.